Chapter 8 From national to international standards in Norway From documents to data? - Ellingsrud, Martin (Taylor & Francis, 2024)
This chapter presents the recent history of Norwegian standardisation within the archives and record management field. Norway was an early proponent of standards in digital archives, the better to promote data exchange and a unified approach to data and records management. Norwegian standards have preceded international standards, including the Noark series that preceded ISO 15489 by decades and the database preservation standard ADDML, which preceded SIARD by several years. This situation started to change particularly around 2010. International standards such as OAIS, METS and PREMIS have been integrated into Norwegian practice through National Archives efforts to develop a "national flavouring" of international standards.As a secondary theme the chapter explores whether standardisation, and to what degree different standards, have promoted an 'archives-as-data' paradigm. The result of this inquiry is mixed. The Noark standards were framed around preserving registries, which are inherently document oriented rather than data oriented, while standards such as ADDML are data oriented. A shift to international standards thus intersects with emerging trends, such as reuse of information and data in public administrations and for research to substitute documents with data.